Standardization of low input technology for cassava - Velmurugan, M; Pugalendhi, L; Kalarani, M K; Manickam, S (JOURNAL OF ROOT CROPS, 2017)
A field experiment was conducted at Tapioca and Castor Research Station, Yethapur during the year 2010 . 2015 with an objective to identify the suitable green manure crop in combination with biofertilizers to improve growth, tuber yield and starch content of cassava. The cassava setts of var. CO (TP) 4 were planted in ridges and furrows method at a spacing of 90 x 75 cm. The green manure crops viz., sunhemp, daincha and cowpea were sown in between two rows of cassava @ 50 kg/ha and the green manure crops were incorporated at 50% flowering (45-50 days after sowing). The biofertilizers viz., Azosprillium (5kg/ha) + Phosphobacteria (5kg/ha) were applied by mixing with well decomposed FYM. The experiment comprised of eight treatments involving green manures and biofertilizers in Randomized Block Design. The results of the experiment revealed that the incorporation of green manure as daincha @50kg/ha + RD of K + 50 % RD of NP + Azosprillium (5kg/ha) + Phosphobacteria (5kg/ha) influenced the tuber yield and total dry matter content than the RDF of FYM (10 t ha-1) + 100:50:150 kg NPK ha-1) (farmers practice). The performance on the growth and tuber yield of cassava was poor (14.53 t ha-1) in the control (without the application of FYM and NPK). However, the incorporation of different green manures did not influence the quality of tubers (starch content).